Influence of live-capture on risk perceptions of habituated samango monkeys - Nowak, Katarzyna; Richards, Shane A.; Roux, Aliza le; Hill, Russell A. (Journal of mammalogy, 2016)
Live-capture of animals is a widely used technique in ecological research, and previously trapped individuals often respond to traps with either attraction or avoidance. The effects of trapping on animals’ risk perception are not often studied, although nonlethal effects of risk can significantly influence animals’ behavior and distribution. We used a combination of experimental (giving-up densities: GUDs) and behavioral (vigilance rates) measures to gauge monkeys’ perceived risk before and after a short livetrapping period aimed at ear-tagging monkeys for individual recognition as part of ongoing research. Two groups of arboreal samango monkeys, Cercopithecus albogularis schwarzi, showed aversion to capture in the form of generalized, group-level trap shyness after 2 individuals per group were cage trapped. We predicted that trapping would increase monkeys’ antipredatory behavior in trap vicinity and raise their GUDs and vigilance rates. However, live-capture led to no perceptible changes in monkeys’ use of space, vigilance, or exploitation of experimental food patches. Height above ground and experience with the experiment were the strongest predictors of monkeys’ GUDs. By the end of the experiment, monkeys were depleting patches to low levels at ground and tree heights despite the trapping perturbation, whereas vigilance rates remained constant. The presence of cage traps, reintroduced in the final 10 days of the experiment, likewise had no detectable influence on monkeys’ perceived risk. Our findings, consistent for both groups, are relevant for research that uses periodic live-capture to mark individuals subject to long-term study and more generally to investigations of animals’ responses to human interventions.